2013
DOI: 10.1088/0004-637x/772/1/70
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATING THE ARRIVAL TIME OF EARTH-DIRECTED CORONAL MASS EJECTIONS AT IN SITU SPACECRAFT USING COR AND HI OBSERVATIONS FROMSTEREO

Abstract: The prediction of the arrival time and transit speed of CMEs near the Earth is one of the key problems in understanding the solar terrestrial relationship.Although, STEREO observations now provide a multiple view of CMEs in the heliosphere, the true speeds derived from stereoscopic reconstruction of SECCHI coronagraph data are not quite sufficient in accurate forecasting of arrival time of a majority of CMEs at the Earth. This is due to many factors which change the CME kinematics, like interaction of two or m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 82 publications
2
83
0
Order By: Relevance
“…In this case, what is seen by a spacecraft is the segment tangent to the line of sight. The triangulation concept has proven to be a useful tool for determining CME Sun-to-Earth kinematics and connecting imaging observations with in situ signatures (e.g., Liu et al 2010aLiu et al ,b, 2011Mishra and Srivastava 2013). Details of when, where, and how CMEs accelerate/decelerate in interplanetary space can be quantified using the kinematics derived with the triangulation method.…”
Section: A Brief Overview Of Cme Kinematicsmentioning
confidence: 99%
“…In this case, what is seen by a spacecraft is the segment tangent to the line of sight. The triangulation concept has proven to be a useful tool for determining CME Sun-to-Earth kinematics and connecting imaging observations with in situ signatures (e.g., Liu et al 2010aLiu et al ,b, 2011Mishra and Srivastava 2013). Details of when, where, and how CMEs accelerate/decelerate in interplanetary space can be quantified using the kinematics derived with the triangulation method.…”
Section: A Brief Overview Of Cme Kinematicsmentioning
confidence: 99%
“…We determine the kinematics of the CME leading front with a triangulation technique 18,19 . This technique has no free parameters and has had success in tracking interplanetary propagation of various CMEs [20][21][22][23][24][25][26] . STEREO B and SOHO provide the best elongation measurements owing to their vantage points, as shown in Fig.…”
Section: Multi-point Imaging Observationsmentioning
confidence: 99%
“…To track and estimate the arrival times of the CMEs in the heliosphere using HI1 & 2 images, we constructed J-maps based on the method developed by Sheeley et al (1999); Davies et al (2009) and derived the variation of elongation of selected features with time. The details about extraction of strip of constant position angle, selection of bin size and adopted procedure for construction of J-maps and derivation of elongation angle from it has been described in section 3.1.1 of Mishra and Srivastava (2013). The positively inclined bright features in the J-maps (Figure 4) correspond to enhanced density structure of the CMEs.…”
Section: Tracking Of Cmes In Hi Field-of-viewmentioning
confidence: 99%
“…Vršnak et al (2013) have shown that drag parameter lies in the range of (0.2 -2.0) × 10 −7 km −1 . Using these values of the drag parameter in the DBM, the arrival time of CME at L1 can be predicted with a reasonably good accuracy (Vršnak et al, 2013;Mishra and Srivastava, 2013). The estimated speed, time and distance (v 0 , t 0 and R ) of LE of CME1 (green track in J-map) are used as inputs in the DBM, corresponding to extreme range of drag parameter, to predict its arrival time and transit speed at L1.…”
Section: Arrival Time Of Tracked Featuresmentioning
confidence: 99%
See 1 more Smart Citation